Identifying and Fostering Gifted University Students Across English Language Skills - Zhussupova, R.F.; Amrenova, A. S.; Abikar Nur, Shamsudin (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Being a gifted and talented learner may mean having academic and creative skills that are above the norm in the classroom. This small-scale study that lasted 12 weeks explored how English language skills (reading, writing, speaking, and listening) in tandem were improved among Kazakhstani Pre-service English teachers. Gardner’s (1983) Multiple Intelligence and Vygotsky’s (1978) Zone of Proximal Development (ZPD) were used as theoretical frameworks. A total of 20 (12 females and 8 males) respondents participated in the study. In addition to the pre-course, mid-term, and post-course English language assessments, each week’s assessment and survey data were collected. The language assessments showed improvement in participants’ language skills; whilst survey data indicated two prevalent themes: the importance of the intervention for professional development and the importance of scaffolding. Limitations of the study included the lack of standardized measurement tools for language assessment. The study recommends further research that involves a larger sample with equal gender representation to enable the generalization of the outcome.